A eficiência do controle social nas licitações e contratos administrativos - Silva Filho, Jesrael Batista da (2017)
The motivation for the development of this survey arose in the importance of recognizing the fundamental right to good public administration as a manifestation of first generation Human Rights, especially as legal instrument aligned with democratic aspirations and the idea of governance, requiring the Public Administration and public managers, the binding of its administrative acts to the concepts of accountability, disclosure, fairness and compliance, mainly in relation to biddings and administrative contracts, in compliance with the constitutional principles of public administration, implicit and explicit, during all contractual stages of the procedure (pre-covenant, development and post-exhaustion - with the duties of objective administrative good faith). However, such principles are often deprecated by the parties in the public adjustments (contractors, contracted, regulators and users), and may entail to deviations of purpose or power. As reaction and preservation, the State instituted forms of institutional and social control to supervise the public management of the resources used in the acquisition of goods, services and public works in its different pre-negotiation modalities. In the same sense, the society has been engaged in the social control constitutionally foreseen by the implementation of the monitoring of public management and its supervision through the use of instruments of social control to provoke judicial control, contained in the legal system, such as Popular Action. The Good administrative practices can contribute to the conquest of the constitutional objectives of our Republic, reflecting improvements in public management, increasing the quality of life of the population and reduction of the social inequalities. In this way, the efficiency of social control instruments in the repression of practices of improbity in the use of public resources is questioned. In the same sense, one inquires about the possibility of effective access of the society to the available control instruments, in order to confer the desired efficiency, and finally, and finally, and finally, to measure this efficiency in the audit activity. In synthesis, the theme of the survey, referring to its central object, the Efficiency of Social Control, adheres to the line of research of Justice and the Efficiency Paradigm in the Master Course in Law of the University Nove de Julho.